Efficiency and Effectivity of The National Zakat Charity Organization (BAZNAS) with Data Envelopment Analysis Method and Allocation to Collection Ratio - Nizar Alam Hamdani; Renita Arta Mevia Sopianti; Mochamad Romdhon (Jurnal Inovasi Bisnis dan Kewirausahaan, 2022)
This study aims to measure the level of efficiency and effectiveness at the National Management Zakat Organization (MZO), Badan Amil Zakat Nasional (BAZNAS), from 2010-2019. In this study, efficiency uses the Data Envelopment Analysis (DEA) method with a Production Approach and an Intermediation Approach, and calculations use the Assumptions of Constants Return to Scale (CRS) and Variable Return to Scale (VRS) with software Frontier Analysis Banxia and Microsoft Excel. The effectiveness of using the Allocation to Collection Ratio (ACR) method compares the total distribution with the collection of Zakat funds. The result showed that the efficiency level using the DEA method in the BAZNAS Organization from 2010 to 2019 had Efficient criteria with the value of the intermediation approach of 98,36% and the production Approach of 97,22%, and level of effectiveness with the ACR Method in the BAZNAS Organization 2010 to 2019 has effective criteria with a value of 95,57%.